Analysis of the Effect of Work Environment and Workload on Work Quality with Work Motivation as an Intervening Variable: Study on Employees of Bank Mandiri KCP Sungai Danau Indonesia - Ridhanoor, Muhammad Rifqi; Meiske Claudia (HM Publisher, 2024)
Work environment and workload are two important factors that can influence employee motivation and work quality. This research aims to analyze and determine the influence of the work environment and workload on work motivation, as well as the influence of work motivation and workload on the work quality of Bank Mandiri KCP Sungai Danau employees. This research uses quantitative methods with a questionnaire as a research instrument. The research sample was 69 employees of Bank Mandiri KCP Sungai Danau, who were selected using a saturated sampling technique. Data were analyzed using structure equation modeling (SEM) analysis techniques with the SmartPLS program. The research results show that the work environment has no significant effect on work motivation, Workload has a significant effect on work motivation, the work environment has a significant effect on work quality, Workload has a significant effect on work quality, Work motivation has no significant effect on work quality, Work environment through motivation work does not have a significant effect on work quality, workload through work motivation does not have a significant effect on work quality. In conclusion, the environment and workload are proven to have a positive influence on work quality, and workload has a positive influence on the work motivation of Bank Mandiri KCP Sungai Danau employees. Work motivation has not been proven to influence work quality.